Técnicas experimentais para a caracterização e avaliação de sistemas de rega de superfície. - Duarte, A.C. (2018)
Submitted by Maria Silva (mfsilva@ipcb.pt) on 2018-01-24T10:38:51Z No. of bitstreams: 1 Agroforum_N.14_5-10.pdf: 1126885 bytes, checksum: 648c2f69395045f2a9d79f37014bbcb2 (MD5)